Implementasi Gerakan Hutan Hijau Bagi Calon Pegantin di Jawa Barat: Analisis Peraturan Gubernur Jawa Barat Nomor 11 Tahun 2025 (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The province of West Java faces ecological pressures due to increasing land conversion, prompting the government to launch the Green Forest Movement for prospective brides and grooms as a community-based environmental conservation strategy. This study aims to examine the implementation of this program at the Haurgeulis Subdistrict KUA (Office of Religious Affairs) and the factors that influence the ecological awareness of prospective brides and grooms. Using descriptive qualitative methods through observation, interviews, and document studies, the research found that the program was implemented through Bimwin socialization, administrative verification, tree seedling delivery, and seedling distribution to the Environmental Agency. Policy adaptation in the form of the obligation to bring one tree seedling increased community affordability and compliance. Positive attitudes toward the environment, the cultural norm of bringing fruit seedlings, perceptions of convenience, and the religious value of Ishlah were found to encourage participation among prospective brides and grooms. However, uneven socialization and the high prevalence of unregistered marriages hindered the program's effectiveness. This study emphasizes the importance of a cultural and adaptive approach in strengthening the implementation of environmental policies at the local level.